Optimalisasi Podcast BISIK dalam Memperkuat Citra dan Preferensi Masyarakat Jawa Barat terhadap RSUD Welas Asih - Ghea Marshanda; Budi Prasetiyo (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2025)
The transformation of digital media has driven a shift in communication strategies within the healthcare service sector, including public hospitals that continue to face challenges in shaping public preferences. RSUD Welas Asih, as one of the public hospitals in West Java, has adopted digital promotion through the live streaming podcast program BISIK (Bincang Sehat Asik) as a medium for health education and the dissemination of health-related information to the public. This study aims to examine the effect of digital promotion through the BISIK program on public preferences toward RSUD Welas Asih, as well as to examine the role of brand image as an intervening variable. This research employs a quantitative approach with a causal research design. Data were collected through the distribution of questionnaires to members of the public who had been exposed to the BISIK program. Data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method to test both direct and indirect relationships among the research variables. The results indicate that digital promotion through the BISIK live streaming podcast has a positive and significant effect on public preferences toward RSUD Welas Asih. Furthermore, brand image is proven to function as a mediating variable that strengthens the influence of digital promotion on public preferences. These findings suggest that digital promotion not only exerts a direct impact but also contributes to the formation of a positive image of public hospitals. This study concludes that well-planned and consistently managed digital promotion can serve as an effective strategy for enhancing public preferences and trust in public healthcare services.